BORDERS AND MINORITIES IN SYRIA: A GEOPOLITICAL ANALYSIS - Giuseppe Bettoni (Bollettino della Società Geografica Italiana, 2019)
Is the Syrian conflict a religious matter? In this conflict the representations “Shiites versus Sunnites” is correct? We will demonstrate that it is not the case and the geopolitical analyses can help to better understand that it is mainly a matter of territory. We underline in this paper the direct relationship between the reasons of this conflict and the unsolved definition of borders at the end of the First World War. The geopolitical methodology, proposed by Yves Lacoste, it’s helpful to better understand the players positions, but also the reasons of a religious representations that is crystallizing the situation.